Transcultural adaptation of the children's anxiety questionnaire in Brazil - Josiane Ramos Garcia Rodrigues; Marla Andréia Garcia deAvila; Milena Temer Jamas; Fernanda Paula Cerantôla Siqueira; Loiane Garcia Daniel; Stefan Nilsson (Wiley, 2021)
Abstract Aim To describe the transcultural adaptation process of the Children's Anxiety Questionnaire (CAQ) for the Brazilian culture. Design This is a methodological study of cross‐cultural adaptation. Methods Study conducted in Brazil and Sweden involved the following steps: preparation, translation, synthesis of translations, back‐translation and review, and harmonization of the translations by a committee of 13 healthcare professionals using the content validity index (CVI). Cognitive debriefing, using children between 4-10 years old, was completed by 15 children to determine if the images corresponded with their meanings and 17 children to determine if they could understand the Global CAQ after listening. Results Convergences and discrepancies between the original instrument in Swedish, the English version and the Brazilian translation were compared. The process of culturally adapting the CAQ to Brazilian Portuguese was validated, as demonstrated by a satisfactory S‐CVI (0.94) among professionals and an agreement of 95% and above by children.